The Impact of Internet on the Reading Habits of Undergraduate Students of Government Hamidia Arts and Commerce College, Bhopal: A Survey (LIS TODAY, 2023)
Reading is a way to get better knowledge of one's own experiences and it can be an  exciting journey to self-discovery. The purpose of this study is to try to understand the  reading habits of undergraduate students of Government Hamidia Arts and Commerce  College, Bhopal and to study the effects of internet on their reading habits. The total number  of students participating in the survey is 150, and the questionnaire was distributed to them  after random sampling. The results reveal whether students enjoy reading, their frequency of  reading books, what genre they prefer to read, the factors that influence their reading habits,  and impact of the internet (ICT) media on their reading habits.
Keywords: Reading Habit; Internet age; Information Technology; Online resources; Reading Behavior; UG students